How to Design and Apply an Objective Structured Clinical Examination (OSCE) in Medical Education? - Said Said Elshama (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
The Objective Structured Clinical Examination (OSCE) is considered a gold standard summative and formative assessment method wherein it is a comprehensive and standardized tool assessing the clinical competencies including psychomotor domain, attitudes, and behaviors that will be manifested in the real work of the medical graduates. Therefore, the implementation of OSCE depends on the design of a blueprint that consists of two axes; the first axis is the tested competencies according to the learning objectives while the second axis represents a system or problem that is related to these competencies. Thus, the blueprint of OSCE is a translation for the learning objectives into clinical competences such as history taking, physical examination, radiographic and laboratory data interpretation, technical skills, attitudinal behaviors, and counseling skills. In addition, the utility index proved that OSCE has a good balance for acceptability, reliability, validity, credibility, feasibility, cost, and educational impact. However, the use of OSCE for the students' assessment is considered expensive and exhausted because it requires many facilities, a great deal of the personnel besides the needed consuming time for its application.